Surviving a time of change: British public schools and Decline and Fall by E. Waugh - N. A. Shatalova (Шаги)
The article attempts to trace the way society’s perception of public schools has reverberated in fiction. We consider the genre of British “school stories” and focus on its most popular specimens in the late 19th — early 20th century. The first novel to be examined in the article is Tom Brown’s Schooldays by Thomas Hughes — a classical “school novel” and a model to be followed for many years to come. However, soon “serious” writers, such as R. Kipling and E.M. Forster, turned to the topic of public schools, using the flaws and problems existing in the system as material for creating plot collisions. This, among other things, testifies to the fact that in the late 19th century elite boarding schools were going through a rough patch – a fact further argued for in sociological studies of the recent decade. The publication of Decline and Fall by Evelyn Waugh, which is analyzed in greater detail in the article, seems to have signaled the end of the “golden era” of public schools and marks a radical shift in their societal status. Since that time public schools have appeared to be in need of justification. Waugh’s novel undermines the very genre of “school” novel by filling the model with subversive content, and, as a result, creating a striking image of a “lost epoch”.